2015
DOI: 10.3109/01913123.2015.1022241
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Aquaporin-3 Role in Nonmelanoma Skin Cancer: An Immunohistochemical Study

Abstract: Aquaporin-3 (AQP3), is an aquaglyceroporin, that plays a role in cell proliferation, tumorigenesis, and cell migration. This study aimed at evaluating the possible role of AQP3 in nonmelanoma skin cancer (NMSC) pathogenesis through its immunohistochemical expression in skin biopsies of these diseases. One-hundred and thirty cutaneous specimens were studied. These included 60 cases of NMSC and 40 normal skin and 30 psoriasis samples, from age- and gender-matched subjects, as a control group. AQP3 was expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Recently, it has been shown that AQP3 expression might be related to development of several carcinomas including gastric carcinoma [26,27], oesophageal and oral squamous cell carcinoma [28], cervical carcinoma [29] and cancers of the thyroid [30], pancreas [31], prostate [32,33], ovary [34] and skin [35,36]. In our study, AQP3 expression was observed in all tissue samples examined in LMS group except in one case.…”
Section: Resultsmentioning
confidence: 50%
“…Recently, it has been shown that AQP3 expression might be related to development of several carcinomas including gastric carcinoma [26,27], oesophageal and oral squamous cell carcinoma [28], cervical carcinoma [29] and cancers of the thyroid [30], pancreas [31], prostate [32,33], ovary [34] and skin [35,36]. In our study, AQP3 expression was observed in all tissue samples examined in LMS group except in one case.…”
Section: Resultsmentioning
confidence: 50%
“…29 However, Verkman et al 30 reported that cultured aortic endothelial cells from wild-type and AQP1-null mice had comparable morphology, growth, and adherence to different surfaces, but showed remarkable impairment in their migration. These findings suggested that endothelial AQP1 expression may facilitate cell migration.…”
Section: Discussionmentioning
confidence: 98%
“…Our results were similar to the studies using anti-AQP3 antibodies prepared from AA180-228 and C terminus peptide of AQP3 in the SCCs of the lung, skin, and oral cavity, UC, prostate adenocarcinoma, and bronchioloalveolar carcinoma (Table 5 ). 17 , 18 , 20 , 29 32 , 34 , 35 , 38 , 39 Degradation of AQP3 protein located near the C terminus part in UC and AA180-228 part of AQP3 in OSCC is associated with a higher grade of the tumors and tumor cell invasion (muscle-invasive UC and OSCC with lymphatic metastasis cases), the underlying molecular mechanism of which remains unclear. 17 , 20 , 34 However, our results were contradictory to those of studies on medullary thyroid carcinoma, hepatocellular carcinoma, pancreatic ductal adenocarcinoma, and triple-negative breast cancer, which suggested increased expression of AQP3 in these carcinomas (Table 5 ).…”
Section: Discussionmentioning
confidence: 99%